The World Refugees Made : Decolonization and the Foundation of Postwar Italy - Ballinger, Pamela, 1968-; Project Muse. (Ithaca : Cornell University Press, 2020)
"Examining the experiences of Italian nationals repatriated from the African and Balkan territories Italy lost with the defeat of fascism, this study rethinks the genesis of both the postwar international refugee regime and Italian decolonization"--
Introduction : mobile histories -- Intermezzo : empire as prelude -- Wartime repatriations and the beginnings of decolonization -- Italy's long decolonization in the era of intergovernmentalism -- Displaced persons and the boundaries of citizenship -- Reclaiming fascism, housing the nation -- Conclusion : we will return.
Description based on print version record.
Keywords: Repatriation; Refugees; Politics and government; Italians; Decolonization; HISTORY -- Europe -- Italy; Decolonisation -- Balkans; Decolonisation -- Afrique; Italiens -- Balkans -- Histoire -- 20e siecle; Italiens -- Afrique -- Histoire -- 20e siecle; Rapatriement -- Italie -- Histoire -- 20e siecle; Refugies -- Italie -- Histoire -- 20e siecle; Decolonization -- Balkan Peninsula; Decolonization -- Africa; Italians -- Balkan Peninsula -- History -- 20th century; Italians -- Africa -- History -- 20th century; Repatriation -- Italy -- History -- 20th century; Refugees -- Italy -- History -- 20th century; Italy; Balkan Peninsula; Africa; Italie -- Politique et gouvernement -- 1945-1976.; Italy -- Politics and government -- 1945-1976.; History; Electronic books